Markov blankets and the preformationist assumption. (29th September 2022) - Dengsø, Mads; Robertson, Ian; Constant, Axel
Abstract: Bruineberg and colleagues argue that a realist interpretation of Markov blankets inadvertently relies upon unfounded assumptions. However, insofar as their diagnosis is accurate, their prescribed instrumentalism may ultimately prove insufficient as a complete remedy. Drawing upon a process-based perspective on living systems, we suggest a potential way to avoid some of the assumptions behind problems described by Bruineberg and colleagues.